Cloning and nucleotide sequence of Pseudomonas aeruginosa DNA gyrase gyrA gene from strain PAO1 and quinolone-resistant clinical isolates. - Kureishi, A (1994)
The Pseudomonas aeruginosa DNA gyrase gyrA gene was cloned and sequenced from strain PAO1. An open reading frame of 2,769 bp was found; it coded for a protein of 923 amino acids with an estimated molecular mass of 103 kDa. The derived amino acid sequence shared 67% identity with Escherichia coli GyrA and 54% identity with Bacillus subtilis GyrA, although conserved regions were present throughout the sequences, particularly toward the N terminus. Complementation of an E. coli mutant with a temperature-sensitive gyrA gene with the PAO1 gyrA gene showed that the gene is expressed in E. coli and is able to functionally complement the E. coli DNA gyrase B subunit. Expression of PAO1 gyrA in E. coli or P. aeruginosa with mutationally altered gyrA genes caused a reversion to wild-type quinolone susceptibility, indicating that the intrinsic susceptibility of the PAO1 GyrA to quinolones is comparable to that of the E. coli enzyme. PCR was used to amplify 360 bp of P. aeruginosa gyrA encompassing the so-called quinolone resistance-determining region from ciprofloxacin-resistant clinical isolates from patients with cystic fibrosis. Mutations were found in three of nine isolates tested; these mutations caused the following alterations in the sequence of GyrA: Asp at position 87 (Asp-87) to Asn, Asp-87 to Tyr, and Thr-83 to Ile. The resistance mechanisms in the other six isolates are unknown. The results of the study suggested that mechanisms other than a mutational alteration in gyrA are the most common mechanism of ciprofloxacin resistance in P. aeruginosa from the lungs of patients with cystic fibrosis.